NKCC1-Deficiency Results in Abnormal Proliferation of Neural Progenitor Cells of the Lateral Ganglionic Eminence - Magalhães, Ana Cathia; Rivera, Claudio (Frontiers in Cellular Neuroscience, 2016)
The proliferative pool of neural progenitor cells is maintained by exquisitely controlled mechanisms for cell cycle regulation. The Na-K-Cl cotransporter NKCC1 is important for regulating cell volume and the proliferation of different cell types in vitro. NKCC1 is expressed in ventral telencephalon of embryonic brains suggesting a potential role in neural development of this region. The ventral telencephalon is a major source for both interneuron and oligodendrocyte precursor cells. Whether NKCC1 is involved in the proliferation of these cell populations remains unknown. In order to assess this question, we monitored several markers for neural, neuronal, and proliferating cells in wild-type and NKCC1 knockout mouse brains. We found that NKCC1 was expressed in neural progenitor cells from the lateral ganglionic eminence (LGE) at E12.5. Mice lacking NKCC1 expression displayed reduced PH3-labeled mitotic cells in the ventricular zone and reduced cell cycle reentry. Accordingly, we found a significant reduction of Sp8-labeled immature interneurons migrating from the dorsal LGE in NKCC1-deficient mice at a later developmental stage. Interestingly, at E14.5, NKCC1 regulated also the formation of Olig2-labeled oligodendrocyte precursor cells. Collectively, these findings show that NKCC1 serves in vivo as a modulator of the cell cycle decision in the developing ventral telencephalon at the early stage of neurogenesis. These results present a novel mechanistic avenue to be considered in the recent proposed involvement of chloride transporters in a number of developmentally related diseases such as epilepsy, autism, and schizophrenia.